LINGUISTICS OF COLOR-DENOTING ADJECTIVES IN MODERN UZBEK POETRY (American Journal of Pedagogical and Educational Research, 2023)
In this article, the linguopoetics of color-denoting adjectives in modern Uzbek poetry is analyzed. The article talks about the essence of the concept of linguopoetics found in Uzbek linguistics today. The evaluation of linguopoetics in Uzbek and world linguistics, different approaches to this phenomenon and scientific works are discussed. This scientific article talks about the essence of the concept of theoretical issues of linguopoetics in Uzbek and world linguistics. The evaluation of linguopoetics in Uzbek and world linguistics, various approaches to this phenomenon, scientific works, and qualities that give color in modern Uzbek poetry are discussed. [1]